PSMA-Targeted Nanotheranostics for Imaging and Radiotherapy of Prostate Cancer - Niranjan Meher; Henry F. VanBrocklin; David M. Wilson; Robert R. Flavell (MDPI AG, 2023)
Targeted nanotheranostic systems offer significant benefits due to the integration of diagnostic and therapeutic functionality, promoting personalized medicine. In recent years, prostate-specific membrane antigen (PSMA) has emerged as an ideal theranostic target, fueling multiple new drug approvals and changing the standard of care in prostate cancer (PCa). PSMA-targeted nanosystems such as self-assembled nanoparticles (NPs), liposomal structures, water-soluble polymers, dendrimers, and other macromolecules are under development for PCa theranostics due to their multifunctional sensing and therapeutic capabilities. Herein, we discuss the significance and up-to-date development of "PSMA-targeted nanocarrier systems for radioligand imaging and therapy of PCa". The review also highlights critical parameters for designing nanostructured radiopharmaceuticals for PCa, including radionuclides and their chelators, PSMA-targeting ligands, and the EPR effect. Finally, prospects and potential for clinical translation is discussed.